Key Plant, Key Pests: Sago Palm (Cycas revoluta) - Juanita Popenoe; Matthew Borden; Adam G Dale; Angela Colonna; Caroline R Warwick; Brian J. Pearson (EDIS)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists, and landscape professionals to help identify common pests associated with common Florida flora. This new 4-page publication of the UF/IFAS Environmental Horticulture Department provides information and general management recommendations for aulacaspis scale, other scales, mealybugs, and manganese deficiency. https://edis.ifas.ufl.edu/ep608